Deadly Emotions - "Colbert, Don." ("Nashville, Tenn. :")
"Pt. 1: The diagnosis: understanding damaging emotions -- What you feel emotionally becomes how you feel physically -- The path from damaging emotion to deadly disease -- Turn off the stress hormones! -- The worst things you can feel for your heart -- Ouch! the link between rage and pain -- Depression isn't ""just in your head"" -- The downward spiral of guilt and shame -- The emotional poison of fear -- When worry turns deadly -- The warping trap of resentment and bitterness -- Pt. 2: The prescription : claiming healthy emotions -- Making the choice for health -- Replacing distortional thinking with truth -- The cleansing power of forgiveness -- The therapeutic value of joy -- Peace can flow like a river of health -- Restoring vitality : the love connection."
Keywords: EMOTIONS - HEALTH ASPECTS.;EMOTIONS - RELIGIOUS ASPECTS.;MIND AND BODY